2023
DOI: 10.1038/s41467-023-42801-6
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone orchestrates glucose-stimulated insulin secretion of pancreatic islets

Yi Cheng,
Hong Zhu,
Jun Ren
et al.

Abstract: Follicle-stimulating hormone (FSH) is involved in mammalian reproduction via binding to FSH receptor (FSHR). However, several studies have found that FSH and FSHR play important roles in extragonadal tissue. Here, we identified the expression of FSHR in human and mouse pancreatic islet β-cells. Blocking FSH signaling by Fshr knock-out led to impaired glucose tolerance owing to decreased insulin secretion, while high FSH levels caused insufficient insulin secretion as well. In vitro, we found that FSH orchestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
4
8
2
Order By: Relevance
“…In addition, our finding of Fshr expression in adipose tissues is consistent with the observations from previous works 12 , 72 . Recently, Fshr expression was reported to be present in -cells of the pancreas to regulate glucosestimulated insulin secretion, further supporting our findings of the Fshr expression pattern 73 .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our finding of Fshr expression in adipose tissues is consistent with the observations from previous works 12 , 72 . Recently, Fshr expression was reported to be present in -cells of the pancreas to regulate glucosestimulated insulin secretion, further supporting our findings of the Fshr expression pattern 73 .…”
Section: Discussionsupporting
confidence: 90%
“…For instance: While this review highlights effects of metabolic hormones on reproductive function, lines of communication between metabolic tissues and the reproductive system are bidirectional, and merit further study. For example, FSH was recently shown to regulate insulin secretion via FSH receptors expressed in pancreatic islets [ 605 ], and gonadal steroid hormones contribute towards sexual dimorphism in energy partitioning and metabolic homeostasis [ 8–10 , 606 ]. Exogenous hormonal contraceptives cause metabolic changes [ 607–609 ], and conversely, the presence of diabetes, obesity, and/or other metabolic disorders has implications for the systemic impacts of hormonal contraceptives [ 610 , 611 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…While this review highlights effects of metabolic hormones on reproductive function, lines of communication between metabolic tissues and the reproductive system are bidirectional, and merit further study. For example, FSH was recently shown to regulate insulin secretion via FSH receptors expressed in pancreatic islets [ 605 ], and gonadal steroid hormones contribute towards sexual dimorphism in energy partitioning and metabolic homeostasis [ 8–10 , 606 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…According to the recent work published in Nature Communications, FSH, through its receptor, regulates glucose-stimulated insulin secretion (GSIS) in pancreatic islets, and high levels of FSH play important roles in postmenopausal diabetes in females. 3 An increasing body of evidence has demonstrated that FSH and its receptor FSHR also have extragonadal effects, including the regulation of fat accumulation, bone mass, and cognitive function. [4][5][6][7] However, limited research has been focused on the effect of FSH on metabolism.…”
mentioning
confidence: 99%
“…According to the recent work published in Nature Communications , FSH, through its receptor, regulates glucose‐stimulated insulin secretion (GSIS) in pancreatic islets, and high levels of FSH play important roles in postmenopausal diabetes in females. 3 …”
mentioning
confidence: 99%